The Effect Of The Use Of Google Classroom Media On Online Science Learning On Environmental Pollution Materials On The Students' Interest And Learning Achievement Of Class Vii Smp - Laela Nurmalia Laela (Universitas Pancasakti Tegal, 2021)
This research was aimed to (1) determine the effect of using google classroom media on th eonline science learning on environmental pollution material towards the learning interest of class VII junior high school students (2) know the effect of using google classroom media on the online science learning on environmental pollution material towards seven grade students of junior high school students achievement (3) know the correlation between interested in learning and learning achievement in online science learning on environmental pollution material for seven grade students of junior high school. The design used in this study was a quasi-experimental type with Posttest-Only Control Design. The population of this study was the entire seventh grade of SMP Negeri 6 Magelang for the academic year 2020/2021 with the total of 6 classes. The sampling technique used was probability sampling technique with the type of simple random sampling. The sample in the study was class VII E and VII F. The results showed that there was an effect of using google classroom media on the online science learning about environmental pollution material on towards the learning interest of seventh grade junior high school students with a high category, there was an effect of using google classroom media on the online science learning environmental pollution material towards learning achievement of seventh grade students. Middle school was in the medium category and there was a correlation between interested in learning and learning achievement on theonline science learning on environmental pollution material for class VII SMP with a strong category.